Determinants of Guest House Yogyakarta Customer Loyalty: A Study of Location, Price, Satisfaction, and Service Quality - Muhammad Rifqi Pratama Rambe; Sumadi Sumadi (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research is generally to determine whether there is an influence of the variables of Location, Price, Satisfaction, and Service Quality on customer loyalty at Guest Houses in Yogyakarta. Specifically, this research aims to analyze the influence of location on customer loyalty, the influence of location on customer satisfaction, the influence of price on customer loyalty, the influence of price on customer satisfaction, the influence of satisfaction on customer loyalty, the influence of service quality on customer satisfaction and the influence of service quality on customer loyalty. The data used is primary data through questionnaires. The number of samples used in this research was 260 respondents. The sampling technique uses a non-probability sampling method which is done by convenience sampling. Data analysis was quantitatively descriptive and SEM analysis using AMOS 25.0. The results of this research indicate that location, price, and service quality have a positive and significant effect on customer satisfaction, and location, price, and service quality have a positive and significant effect on customer loyalty at the Yogyakarta Guest House.